PERBANDINGAN GAYA DIPLOMASI ANTARA PEMERINTAHAN GEORGE W. BUSH DAN BARRACK OBAMA DALAM MENGHADAPI ISUE TERRORISME - Haqqi, Halifa (Transformasi, 2012)
Abstract Last decade, The US Government led by two different type of president, George Walker Bush and Barrack Obama. George W. Bush known as Republicant and Barrack Obama from Democrats. Both had different style of diplomacy especially on the terrorism issued. The background of family, education and party became main factors the style of diplomacy. President George W Bush partial to hard politics, preemptive strike and defensive intervention. In addition, decision President Barrack Obama consider by Soft Diplomacy, balanced dan smooth. Keywords : Diplomacy, Terrorism.